1977
DOI: 10.1111/j.1365-2621.1977.tb12615.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Residual Amylose on Floccing of Granulated Cane Sugar

Abstract: The purpose of this research was to ascertain the nature of the material in granulated cane sugar which causes flocculation in acidified sugar syrups, and is, consequently, undesirable in bottled beverages. The acid and alcohol floes of 12 sugar samples were examined for their amino acid content. Floccing sugars contained a higher concentration of amino acids than nonfloccers. Isolation techniques were developed for the floe-causing substance (FCS) using ion-exchange column chromatography. Characterization stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1982
1982
1982
1982

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Research to detect the FCS has narrowed the possibilities to protein and an amylose derivative (Cohen et al, 1970; Liuzzo and Hsu, 1975). Liuzzo et al (1977) reported that the amino acid content of floe was directly related to the flooring occurrences of sugar. These workers concluded that the FCS in granulated cane sugar was due to an amylose-related substance which can complex a number of other compounds to enhance the floe formation, especially trace protein.…”
mentioning
confidence: 99%
“…Research to detect the FCS has narrowed the possibilities to protein and an amylose derivative (Cohen et al, 1970; Liuzzo and Hsu, 1975). Liuzzo et al (1977) reported that the amino acid content of floe was directly related to the flooring occurrences of sugar. These workers concluded that the FCS in granulated cane sugar was due to an amylose-related substance which can complex a number of other compounds to enhance the floe formation, especially trace protein.…”
mentioning
confidence: 99%